DIAGNOSIS OF BOVINE LEPTOSPIROSIS BY 16s rRNA BASED POLYMERASE CHAIN REACTION - Balakrishna, G; Minambigai, TV; Roy, Parimal (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The present study was undertaken to diagnose acute case of bovine leptospirosis by PCR. A total of 115 serum samples collected from clinically suspected (33 cattle and 32 buffaloes) and apparently healthy (50) buffaloes were subjected to PCR. Among the clinically suspected animals, the PCR detected leptospiral DNA in 21 (32.31 per cent) samples. The clinical signs in these positive cases included abortion, repeat breeders, jaundice and haemorrhagic mastitis. Apparently healthy animals also gave positive results in PCR (6.00 per cent) which might be due to subclinical leptospirosis.